Triple combination antibiotic therapy for carbapenemase-producing Klebsiella pneumoniae: a systematic review. Issue 1 (December 2017) - Jacobs, David; Safir, M.; Huang, Dennis; Minhaj, Faisal; Parker, Adam; Rao, Gauri
Abstract Background The spread of carbapenemase-producingK. pneumoniae (CPKP) has become a significant problem worldwide. Combination therapy for CPKP is encouraging, but polymyxin resistance to many antibiotics is hampering effective treatment. Combination therapy with three or more antibiotics is being increasingly reported, therefore we performed a systematic review of triple combination cases in an effort to evaluate their clinical effectiveness for CPKP infections. Methods The PubMed database was searched to identify all published clinical outcomes of CPKP infections treated with triple combination therapy. Articles were stratified into two tiers depending on the level of clinical detail provided. A tier 1 study included: antibiotic regimen, regimen-specific outcome, patient status at onset of infection, and source of infection. Articles not reaching these criteria were considered tier 2. Results Thirty-three studies were eligible, 23 tier 1 and ten tier 2. Among tier 1 studies, 53 cases were included in this analysis. The most common infection was pneumonia (31%) followed by primary or catheter-related bacteremia (21%) and urinary tract infection (17%). Different combinations of antibiotic classes were utilized in triple combinations, the most common being a polymyxin (colistin or polymyxin B, 86.8%), tigecycline (73.6%), aminoglycoside (43.4%), or carbapenem (43.4%). Clinical and microbiological failure occurred in 14/39 patients (35.9%) and 22/42 patients (52.4%), respectively. Overall mortality for patients treated with triple combination therapy was 35.8% (19/53 patients). Conclusions Triple combination therapy is being considered as a treatment option for CPKP. Polymyxin-based therapy is the backbone antibiotic in these regimens, but its effectiveness needs establishing in prospective clinical trials.